Hubungan Perilaku Pemberantasan Sarang Nyamuk Dengan Densitas Larva Nyamuk Di SMPS Dayah Darul Yaqin Kota Lhokseumawe Tahun 2022 - Sofia, Rizka; Sahputri, Juwita; Ananda, Yuanita (LPPM Universitas Almuslim, 2024)
Transmission of disease by mosquito vectors is influenced by mosquito density, so the first step to eradicate this disease is to observe the existing larvae. Mosquito larvae can be prevented by eradicating mosquito nests. This study aims to determine the relationship between mosquito eradication behavior and density of mosquito larvae in Dayah Darul Yaqin Middle School, Lhokseumawe City in 2022. The research method used was observational analytic through a cross sectional approach. Sampling in this study used a stratified random sampling technique as many as 123 students who met the inclusion and exclusion criteria. The results of this study obtained a description of the behavior of eradicating mosquito nests with the highest level at a sufficient level of 61 respondents (49.6%). The density of mosquito larvae in the students' bathrooms showed a high distribution rate (75%) while in the female students' bathrooms the results were low (25%). The result of the container index (CI) measurement is 64.28% which has a density figure of 9. The results of the Spearman test analysis obtained a p value = 0.002 and a correlation coefficient (r) value of 0.276. The conclusion of this study is that there is a relationship between mosquito eradication behavior and the density of mosquito larvae in Dayah Darul Yaqin Middle School, Lhokseumawe City in 2022.